Phase noise analysis of the connected-sources parallel quadrature oscillator. (June 2021) - Jafari, Bahram; Sheikhaei, Samad
Highlights: A novel phase noise analysis of the Connected Sources Parallel Quadrature Oscillator (CSPQO) is proposed. Using a new perspective, closed-form expressions have been derived for its amplitude, ISF, NMF, and phase noise. Based on simulation results, there are less than 2% and 1dB calculation errors for oscillation amplitude and phase noise. The proposed analysis gives circuit designers a deep insight into CSPQO's performance to achieve the most favorable design. It is shown that a coupling factor of 0.35 is an optimum point for CSPQO to have a better performance compared to DSPQO. Abstract: In this work, the operation mechanism of the Connected-Sources Parallel Quadrature Oscillator (CSPQO) is investigated meticulously through a novel perspective. It is proven that, unlike Disconnected-Sources Parallel Quadrature Oscillator (DSPQO), conduction angles of the switching and coupling transistors vary versus the coupling factor in CSPQO. This perspective leads to formulating CSPQO's drain currents to derive closed-form expressions for its phase noise for the first time. A comprehensive phase noise analysis for CSPQO is presented using Hajimiri's phase noise theorem. There are less than 2% and 1dB errors for oscillation amplitude and phase noise calculations. Besides, an inclusive comparison is performed between DSPQO and CSPQO, and it is established that CSPQO has a better performance for coupling factors less than 1. It is shown that a coupling factor of 0.35 is an optimum design point for CSPQO to have better phase noise and Figure of Merit (FoM) performances compared to DSPQO. Graphical abstract: Image, graphical abstract